The Ghost Sitter - Griffin, Peni R (New York : Scholastic Inc., 2002)
When she realizes that her new house is haunted by the ghost of a ten-year-old girl who used to live there, Charlotte tries to help her find peace.
"This edition is only available for distribution through the school market."--P.[4] of cover.
700L
81682
Keywords: Ghost -- Fiction; Siblings -- Fiction; Mystery